PERSEPSI PENGGUNA INSTAGRAM SEBAGAI MEDIA PROMOSI GEDUNG SENTRA TENUN JEMBRANA - Cantika Jesy Parsadela, Ni Made; Suardana, I Wayan; Dewi, NGAS. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 12 No 2 (2024): Jurnal IPTA (December 2024), 2025)
Almost two years the opening of the Jembrana Weaving Center Building, the manager felt that visits were erratic every day and the number of Instagram followers did not increase much. It is necessary to evaluate the promotional strategy applied and immediately improve its weaknesses. The evaluation uses the AIDA model reference to measure the effectiveness of Instagram social media as a promotional medium. The sampling technique uses purposive sampling method and informants purposive method. Data collection techniques through distributing questionnaires to 85 respondents. The data analysis technique is descriptive quantitative using the average score analysis technique, validity test, reliability test, standard deviation, and simple tabulation. The results showed that the characteristics of visitors based on geographical aspects were dominated by Indonesian citizenship,; demographic aspects are dominated by age 21-30 years, male gender, occupation as a student, undergraduate education level, and unmarried status; psychographic aspects, the respondent's source of information is recommended from friends / relatives, using Instagram for 2-3 hours a day and new followers who follow> 1 month, see Instagram post views once a week, the purpose of visiting is to fill spare time.  The results of visitors' perceptions of Instagram social media as a promotional medium are in the “Effective” category with a scale range of 4,04– 4,24, and an overall average of 4,14. It can be concluded that the use of Instagram social media as a promotional media is effective and it is hoped that future Instagram management can be better.